Measuring Spatial Ability for Talent Identification, Educational Assessment, and Support: Evidence from Adolescents with High Achievement in Science, Arts, and Sports - Anna V. Budakova; Maxim V. Likhanov; Teemu Toivainen; Alexey V. Zhurbitskiy; Elina O. Sitnikova; Elizaveta M. Bezrukova; Yulia Kovas (Psychology in Russia: State of Art, 2021)
Background. Spatial ability (SA) is a robust predictor of academic and occupational achievement. The present study investigated the psychometric properties of 10 tests for measuring of SA in a sample of talented schoolchildren.